Combined antihypertensive therapy in patients with chronic obstructive pulmonary disease - M. V. Matsievich; T. V. Adasheva; V. S. Zadionchenko; V. Z. Lankin; A. K. Tikhadze; G. G. Konovalova; I. V. Fedorova; G. A. Nakhaeva; Z. O. Grineva; K. M. Bagatyrova; V. V. Li (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To investigate endothelium-regulating and antioxidant effects of trandolapril and verapamil SR combination (Tarka) in patients with arterial hypertension (AH) and chronic obstructive pulmonary disease (COPD).Material and methods. In total, 42 COPD and AH patients, aged 48-70 years, were examined. All participants received continuous basis COPD treatment and 16-week Tarka therapy. At baseline and at the end of the study, lung function, systemic inflammation, oxidative stress and antioxidant potential parameters were measured.Results. All patients achieved office-measured target blood pressure (BP) levels. Bronchial conductivity increase was explained by therapy-associated improvement in pulmonary hemodynamics. The medication was safe and well-tolerated by patients with COPD and AH. Decrease in C-reactive protein levels, possibly explaining antiinflammatory medication effect, pointed to the suppression of endothelium-damaging influences. The treatment was also associated with decreased lipid peroxidation, reduced serum levels of acylhydroperoxides, and increased concentration and activity of antioxidant enzymes.Conclusion. AH and COPD therapy should include antihypertensive agents with pleiotropic effects, specifi- cally, suppressing systemic inflammation, correcting endothelial function, and enhancing antioxidant potential. These characteristics could act as additional criteria of AH treatment effectiveness in patients with combined cardiovascular and respiratory pathology.